2011
DOI: 10.1038/aps.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylenastron suppresses human pancreatic cancer cell migration and invasion in vitro via allosteric inhibition of mitotic kinesin Eg5

Abstract: Aim:The mitotic kinesin Eg5 plays a critical role in bipolar spindle assembly, and its inhibitors have shown impressive anticancer activity in preclinical studies. This study was undertaken to investigate the effect of dimethylenastron, a specific inhibitor of Eg5, on the migration and invasion of pancreatic cancer cells. Methods: Human pancreatic cancer cell lines PANC1, EPP85, BxPC3, CFPAC1, and AsPAC1 were used. Eg5 expression was examined using immunofluorescence microscopy. Cell migration and invasion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…These changes in the cytoskeleton are most likely responsible for the reduced migratory and adhesive capacity after Eg5 inhibition. Just recently, it has been shown that Eg5 also has a function in normal and malignant cell migration [14, 15]. There is evidence from the literature that DMN is highly specific for Eg5 kinesin, it binds to a region of the protein composed of loop 5, helix α2 and α3, which is not conserved in other kinesins [34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in the cytoskeleton are most likely responsible for the reduced migratory and adhesive capacity after Eg5 inhibition. Just recently, it has been shown that Eg5 also has a function in normal and malignant cell migration [14, 15]. There is evidence from the literature that DMN is highly specific for Eg5 kinesin, it binds to a region of the protein composed of loop 5, helix α2 and α3, which is not conserved in other kinesins [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Beside their role in mitosis, an increasing number of reports point to the possibility that they may exert other biological functions. KIF11/Eg5 plays an important role in normal and cancer cell migration [14, 15]. Only recently, an important role of Eg5 in protein translation has been discovered [16] and KIF4A has been shown to be implicated in neuronal survival [17].…”
Section: Introductionmentioning
confidence: 99%
“…STLC tightly binds to Eg5 to disrupt the mitotic spindle during metaphase without direct influences on microtubule dynamics [34,39,40]. Dimethylenastron allosterically inhibits Eg5 through decreasing ADP release [41,42]. These three cell-permeable inhibitors are effective tools for the long-term inhibition of Eg5 in vivo.…”
Section: Eg5 Proteins Locate At the Cytoplasm And Spindle Microtubulementioning
confidence: 99%
“…The final concentrations of each specific inhibitor are listed as follows. The concentrations of Monastrol [19,40], STLC [37], and Dimethylenastron [41,63] were chosen according to previous studies. For Eg5 inhibition in mouse testes, Monastrol (50 μM), STLC (10 μM) and Dimethylenastron (20 μM) were used, respectively.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…KIF11 is found to be significantly associated with tumour stage, grade and poor survival for patients with renal cell carcinoma (Sun et al, 2013). Up-regulation of KIF11 has also been reported in pancreatic cancer cells (Sun et al, 2011).…”
Section: Kif11mentioning
confidence: 93%